2015
DOI: 10.1177/000313481508100118
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglossal Duct Carcinoma

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…By extension, however, the presence of a thyroid follicular based neoplasm, suggests thyroid gland tissue origin. Further, as carcinoma was only identified in four patients who also had a thyroidectomy [10,37,39,43] it seems to confirm a primary origin from ectopic thyroid gland tissue rather than representing metastatic disease. Other considerations would include a papillary thyroid carcinoma arising in the pyramidal lobe of the thyroid gland or metastatic carcinoma to the Delphian lymph node, but these considerations can be easily excluded by clinical and pathology findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By extension, however, the presence of a thyroid follicular based neoplasm, suggests thyroid gland tissue origin. Further, as carcinoma was only identified in four patients who also had a thyroidectomy [10,37,39,43] it seems to confirm a primary origin from ectopic thyroid gland tissue rather than representing metastatic disease. Other considerations would include a papillary thyroid carcinoma arising in the pyramidal lobe of the thyroid gland or metastatic carcinoma to the Delphian lymph node, but these considerations can be easily excluded by clinical and pathology findings.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, TGDC associated malignancies are infrequently identified by FNA, primarily due to the inherently hypocellular nature of the specimen and failure to adequately sample the malignant component, which often comprises a small area of a predominantly cystic lesion [4,50,[73][74][75][76]. Among the reported pediatric patients with TGDC carcinoma, FNA was performed in five, and not performed in our patients [13,37,38,42,48]. One was interpreted as a thyroglossal duct cyst [13] three were atypical or suspicious for malignancy [37,38,42] and one was diagnosed as a papillary thyroid carcinoma [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of all the cases that had total thyroidectomies, either as a concurrent or staged operation, only Pezzolla, et al (2015) reported positive findings of an incidental synchronous thyroid adenocarcinoma. Chrisoulidou, et al (2013) performed a total thyroidectomy subsequently as a result of TGDCa recurrence.…”
Section: Discussionmentioning
confidence: 99%